1991
DOI: 10.1177/026010609100700204
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Practices Affect Arthritis

Abstract: It has been suggested that boron deficiency in food may be a cause of some arthritis (Newnham 1979). Epidemiological studies were done to try to ascertain why some countries have more or less arthritis than other countries. Jamaica, Mauritius, Fiji and Israel were visited with a view to ascertaining the boron levels of locally consumed food as it was suspected that excessive use of soluble chemical fertilizers had damaged the soils of the sugar producing lands. Food grown on these soils were found to have low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
9
0
3
Order By: Relevance
“…Over 50 years of research has concluded that boron is essential for healthy bones and joints . Researchers have also observed that there is a difference in the concentration of boron in arthritic bones (3 ppm) and in healthy bones (56 ppm) . The presence of boron has an influence in a variety of metabolic actions, and it is known that boron interacts with calcium, vitamin D, and magnesium which are all significant for the bone metabolism process .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 50 years of research has concluded that boron is essential for healthy bones and joints . Researchers have also observed that there is a difference in the concentration of boron in arthritic bones (3 ppm) and in healthy bones (56 ppm) . The presence of boron has an influence in a variety of metabolic actions, and it is known that boron interacts with calcium, vitamin D, and magnesium which are all significant for the bone metabolism process .…”
Section: Discussionmentioning
confidence: 99%
“…25 Researchers have also observed that there is a difference in the concentration of boron in arthritic bones (3 ppm) and in healthy bones (56 ppm). 26 The presence of boron has an influence in a variety of metabolic actions, and it is known that boron interacts with calcium, vitamin D, and magnesium which are all significant for the bone metabolism process. 27 Although the underlying mechanisms of the B activity are still being investigated, in recent years, scientists have started to exploit boron-based BG for bone TE applications.…”
Section: Discussionmentioning
confidence: 99%
“…A between country comparison suggests that the prevalence of arthritis is inversely proportional to the level of boron in soil and subsequently the food supply [38]. Given the effect of boron on steroid hormone metabolism, it may also impact on arthritis by increasing the synthesis of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Boron could counteract the effect of peroxide. A possible explanation might be the ability of boron to prevent free radical mediated damage in vivo, which has been demonstrated earlier [22,24]. Size exclusion chromatography of iron-containing proteins exposed to peroxides indicates a change in the elution volume (V e ) of Cyt c (Fig.…”
Section: Discussionmentioning
confidence: 55%